Financial literacy and classroom practices among early childhood and elementary teachers in India and the US. Issue 6 (18th August 2019) - Jayaraman, J. D.; Jambunathan, Saigeetha; Adesanya, Regina
ABSTRACT: This study compared the financial literacy and teaching practices of 82 early and elementary teachers in India and US using a 43-item survey. Analysis showed that financial literacy of Indian teachers was lower than their American counterparts. Teachers in India enjoyed teaching financial literacy more than teachers in the US. Indian teachers received more professional development training than American teachers. Indian teachers reported using the school store, children's literature and pictorial worksheets while American teachers reported using learning centres, play money, fake credit cards, technology and games to teach financial literacy.